SEBS-based foamed plastic elastomer and preparation method thereof
By adjusting the ratio of SEBS and other materials, combined with twin-screw extrusion technology, the problems of formamide residue and irritating odor in SEBS foamed plastic materials are solved, and SEBS-based hair with odorless, low volatile organic matter and excellent mechanical properties are achieved Foam plastic materials meet the standards of modern green industry development.
Patent Information
- Application Number
- CN202411241560.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
The existing SEBS foam plastic materials have problems with formamide residues, irritating odors and health hazards, and chemical substances that do not conform to the development of modern green industry are used during the production process.
Using SEBS-based foam plastic material, by adjusting the linear and nonlinear chain structure ratio of SEBS, combined with paraffin oil, antioxidants, ultraviolet absorbers, expanded microspheres, ASA resin, ABS resin, PP resin and heavy calcium powder. The molding was performed using a twin-screw extruder, which avoided vulcanized cross-linking and VOC emissions, and achieved the properties of formamide-free, odorless and low volatile organic matter.
The excellent mechanical properties and elastic recovery ability of SEBS-based foamed plastic materials are achieved, with tensile strength of 0.9-1.4MPa, elongation of breaking is 160-220%, surface hardness is 40A-55A, and the average pore diameter of the bubble cell is 72.1- 96.2μm, and the total volatile organic matter is less than 4.2mg/(m2·h), which meets the requirements of green industry development.
Smart Images

Figure CN119307108A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermoplastic elastomer foaming, and in particular to a SEBS-based foamed plastic elastomer and a preparation method thereof. Background Art
[0002] Thermoplastic SEBS elastomers present a multiphase condensed structure with amorphous polystyrene blocks as "physical" crosslinking points at the use temperature. They have the characteristics of both plastics and rubbers, and have excellent toughness, mechanical properties, stress cracking resistance, and weather resistance. Compared with the monomer residues or free isocyanates produced by hydrolysis of thermoplastic TPU elastomers during use, SEBS does not involve hydrolysis and has chemical stability in wet environments. Therefore, SEBS elastomers can be widely used in industries such as prefabricated plastic tracks, yoga mats, and plastic coatings for sports equipment.
[0003] The good impact absorption performance and elastic recovery ability of the plastic track can effectively absorb the potential energy of movement and reduce the impact force; at the same time, the plastic deformation caused by the impact can be quickly recovered, effectively protecting the limbs and joints of the athletes. CN117986793A and CN 117050457A disclose hydrogenated butadiene-styrene copolymer / ethylene-vinyl acetate copolymer composite foaming material and molded foaming process; these two patent applications use azodicarbonamide as a foaming agent and diisopropylbenzene peroxide (or di-tert-butyl peroxide diisopropylbenzene) as a crosslinking agent in the material formula, and the foamed products have residual formamide and a pungent odor, which is not friendly to the human body and the environment, and does not conform to the concept of modern green industrial development. CN117986793A discloses a polyether TPU / SEBS / EVA composite foaming material and a supercritical carbon dioxide physical microporous foaming process. The foamed particles involved in the patent application have a stabilization time of 20 to 48 hours and low production capacity. CN117986793A discloses a supercritical foaming process and SEBS foamed plastic. The foaming process requires the use of a large amount of toluene, as well as residual toluene in the SEBS foamed plastic. Toluene will greatly harm the health of production personnel and foamed plastic users, and is not in line with the concept of modern green industrial development. Summary of the invention
[0004] The purpose of the present invention is to provide a SEBS-based foamed plastic elastomer and a preparation method thereof. The elastomer material has no formamide residue, no sulfur, and no taste. No vulcanization and cross-linking are required during the preparation process, and no VOC emissions are emitted at its processing temperature and use temperature.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In one aspect, the present invention provides a SEBS-based foamed plastic elastomer, which is made of the following components in parts by weight:
[0007]
[0008] Preferably, the SEBS elastomer is composed of non-linear chain structure SEBS and linear chain structure SEBS, wherein the mass percentage of the linear chain structure SEBS is 0-30%.
[0009] Preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant DSTP, and antioxidant 618.
[0010] Preferably, the ultraviolet absorber is selected from one or more of UV 531, UV 770, UV 326, UV 2020, and UV 119.
[0011] On the other hand, the present invention also provides a method for preparing the above-mentioned SEBS-based foamed plastic elastomer, comprising the following steps: weighing SEBS and paraffin oil according to a ratio, stirring and mixing at high speed for 8 minutes; adding an antioxidant and an ultraviolet absorber, stirring at high speed for 3 minutes; adding expanded microspheres, stirring at high speed for 3 minutes; adding ASA resin, ABS resin, PP resin, PE wax and heavy calcium powder, stirring and mixing at high speed for 6 minutes to obtain a mixture; and extruding the mixture into shape through a twin-screw extruder.
[0012] Preferably, the rotation speed of the high-speed stirring in each step is 450±10 rpm.
[0013] Preferably, the temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0014] The SEBS-based foamed plastic elastomer of the present application is prepared by adjusting the relative proportion of the linear and nonlinear chain structures of SEBS, and coordinating the relative proportion, size and distribution of the PS amorphous dispersed phase and the PP crystalline dispersed phase, so as to regulate the physical cross-linked network structure in the viscosity-flow transition zone of the composite material, so that it has both effective cell locking and control ability and melt strength suitable for screw extrusion; adjusting the relative proportion of polar groups with different polarities and the relative proportion of the linear and nonlinear chain structures of SEBS, coordinating to stabilize the cells, regulating the pore size of the cells, and making it have excellent elastic recovery; coordinating the melt strength, the foaming temperature and the foaming rate of the expanded microspheres, so that the melt can inhibit the foaming of the expanded microspheres in the screw conveying section and the melting section, so that the expanded microspheres expand in the homogenization section, and the gas dissolved in the melt forms a foaming nucleus in the die head, and the melt has a suitable melt strength, which can just lock the gas in the bubble and prevent gas escape.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The SEBS-based foamed plastic elastomer provided by the present invention has no formamide residue, no sulfur, no taste, and the total volatile organic matter is less than 4.2 mg / (m 2 h).
[0017] (2) The SEBS-based foamed plastic elastomer provided by the present invention has excellent mechanical properties and elastic recovery, a tensile strength of 0.9-1.4 MPa, and an elongation at break of 160-220%.
[0018] (3) The surface hardness of the SEBS-based foamed plastic elastomer provided by the present invention is 40A-55A, and the apparent density is 0.59-0.75g / cm 3 .
[0019] (4) The average pore size of the SEBS-based foamed plastic elastomer provided by the present invention is between 72.1 and 96.2 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Example 1;
[0021] Figure 2 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Example 2;
[0022] Figure 3 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Example 3;
[0023] Figure 4 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Example 4;
[0024] Figure 5 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Example 5;
[0025] Figure 6 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Comparative Example 1;
[0026] Figure 7 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Comparative Example 2;
[0027] Figure 8 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Comparative Example 3;
[0028] Fig. 9 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Comparative Example 4;
[0029] Fig.10 This is a scanning electron microscope image of the SEBS-based foamed plastic elastomer prepared in Comparative Example 5. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] Unless otherwise specified, the raw materials used in the following examples are commercially available products.
[0032] The paraffin oil is saturated paraffin oil, and the kinematic viscosity at 40°C is 100-160 mm 2 / s.
[0033] The melt flow index of the ASA resin is 20 g / 10 min (190° C. / 2.16 kg).
[0034] The ABS resin contains 20-25 wt.% acrylonitrile and has a melt flow index of 37-43 g / 10 min (220° C. / 10 kg).
[0035] The PP resin has an average molecular weight of 8000-11000 and a melting point of 165-175°C.
[0036] The particle size of the heavy calcium powder is 1000 mesh to 2500 mesh.
[0037] The particle size of the expanded microspheres is 28-40 microns, the starting temperature is 165-175°C, and the maximum temperature is 200-210°C.
[0038] The antioxidant consists of antioxidant 1010 and antioxidant 168, and the mass ratio of the antioxidant 1010 and the antioxidant 168 is 2:1.
[0039] The ultraviolet absorber consists of UV 531 and UV 770, and the mass ratio of the two is 2:1.
[0040] Example 1
[0041] 20Kg nonlinear SEBS and 36Kg paraffin oil were mixed by high-speed stirring for 8 minutes; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.2Kg UV 531 and 0.1Kg UV 770 were added in sequence and stirred at high speed for 3 minutes; 1Kg expanded microspheres were added and stirred at high speed for 3 minutes; 1.6Kg ASA resin, 1.6Kg ABS resin, 2Kg PP resin, 0.6Kg PE wax and 4Kg heavy calcium powder were added and stirred at high speed for 6 minutes to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0042] Example 2
[0043] 16Kg nonlinear SEBS, 4Kg linear SEBS and 38Kg paraffin oil were mixed by high-speed stirring for 8 minutes; 0.27Kg antioxidant 1010, 0.13Kg antioxidant 168, 0.2Kg UV 531 and 0.1Kg UV 770 were added and stirred at high speed for 3 minutes; 0.8Kg expanded microspheres were added and stirred at high speed for 3 minutes; 2Kg ASA resin, 1.6Kg ABS resin, 2.4Kg PP resin, 0.6Kg PE wax and 5Kg heavy calcium powder were added and stirred at high speed for 6 minutes to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0044] Example 3
[0045] 18Kg nonlinear SEBS, 2Kg linear SEBS and 40Kg paraffin oil were mixed by high-speed stirring for 8min; 0.27Kg antioxidant 1010, 0.13Kg antioxidant 168, 0.27Kg UV 531 and 0.13Kg UV 770 were added and stirred at high speed for 3min; 0.2Kg expanded microspheres were added and stirred at high speed for 3min; 2Kg ASA resin, 2Kg ABS resin, 2.4Kg PP resin, 0.4Kg PE wax and 3Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0046] Example 4
[0047] 14Kg nonlinear SEBS, 6Kg linear SEBS and 20Kg paraffin oil were mixed by high-speed stirring for 8min; 0.133Kg antioxidant 1010, 0.067Kg antioxidant 168, 0.2Kg UV 531 and 0.1Kg UV 770 were added and stirred at high speed for 3min; 0.6Kg expanded microspheres were added and stirred at high speed for 3min; 1.2Kg ASA resin, 1Kg ABS resin, 3Kg PP resin, 0.5Kg PE wax and 4.5Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0048] Example 5
[0049] 15Kg nonlinear SEBS, 5Kg linear SEBS and 30Kg paraffin oil were mixed by high-speed stirring for 8 minutes; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.133Kg UV 531 and 0.067Kg UV 770 were added and stirred at high speed for 3 minutes; 0.5Kg expanded microspheres were added and stirred at high speed for 3 minutes; 1Kg ASA resin, 1.2Kg ABS resin, 2Kg PP resin, 0.6Kg PE wax and 3.5Kg heavy calcium powder were added and stirred at high speed for 6 minutes to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0050] Comparative Example 1
[0051] 4Kg nonlinear SEBS, 16Kg linear SEBS and 40Kg paraffin oil were mixed by high-speed stirring for 8min; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.2Kg UV 531 and 0.1Kg UV 770 were added and stirred at high speed for 3min; 1.2Kg expanded microspheres were added and stirred at high speed for 3min; 0.8Kg ASA resin, 0.8Kg ABS resin, 1.6Kg PP resin, 0.6Kg PE wax and 3.5Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0052] Comparative Example 2
[0053] 6Kg nonlinear SEBS, 14Kg linear SEBS and 35Kg paraffin oil were mixed by high-speed stirring for 8min; 0.27Kg antioxidant 1010, 0.13Kg antioxidant 168, 0.27Kg UV 531 and 0.13Kg UV 770 were added and stirred at high speed for 3min; 0.16Kg expanded microspheres were added and stirred at high speed for 3min; 2.4Kg ASA resin, 2.4Kg ABS resin, 1.6Kg PP resin, 0.5Kg PE wax and 5Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0054] Comparative Example 3
[0055] 8Kg nonlinear SEBS, 12Kg linear SEBS and 30Kg paraffin oil were mixed by high-speed stirring for 8min; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.2Kg UV 531 and 0.1Kg UV 770 were added and stirred at high speed for 3min; 1.2Kg expanded microspheres were added and stirred at high speed for 3min; 0.8Kg ASA resin, 0.8Kg ABS resin, 3.2Kg PP resin, 0.5Kg PE wax and 3Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0056] Comparative Example 4
[0057] 15Kg nonlinear SEBS, 10Kg linear SEBS and 40Kg paraffin oil were mixed by high-speed stirring for 8min; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.27Kg UV 531 and 0.13Kg UV 770 were added and stirred at high speed for 3min; 0.16Kg expanded microspheres were added and stirred at high speed for 3min; 2.4Kg ASA resin, 0.8Kg ABS resin, 3.2Kg PP resin, 0.5Kg PE wax and 4Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0058] Comparative Example 5
[0059] 10Kg nonlinear SEBS, 10Kg linear SEBS and 40Kg paraffin oil were mixed by high-speed stirring for 8min; 0.2Kg antioxidant 1010, 0.1Kg antioxidant 168, 0.27Kg UV 531 and 0.13Kg UV 770 were added and stirred at high speed for 3min; 0.5Kg azodicarbonamide, 0.4Kg diisopropylbenzene peroxide and 0.02Kg zinc oxide were added and stirred at high speed for 3min; 2.4Kg ASA resin, 2.4Kg ABS resin, 3.2Kg PP resin, 0.5Kg PE wax and 4Kg heavy calcium powder were added and stirred at high speed for 6min to obtain a mixture. The speed of high-speed stirring in each step was 450±10 rpm. The mixed material is extruded into shape by a twin-screw extruder. The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
[0060] Scanning electron microscopy was used to analyze the morphology of the samples. Figure 1-Figure 5 The SEM images of SEBS-based foamed plastic elastomers prepared in Examples 1-5 of the present invention are respectively: Figure 6-Figure 10 They are SEM images of SEBS-based foamed plastic elastomers prepared in Comparative Examples 1-5 of the present invention respectively.
[0061] The volatile organic compound content of the samples was determined according to GB / T 23986-2009.
[0062] According to GB / T 10654-2001, the tensile strength and elongation at break of the specimens were tested using an electronic universal testing machine at a tensile rate of 5 mm / min. Each group of specimens was tested 5 times in parallel and the average value was taken.
[0063] Refer to GB / T 6343-2009, test the apparent density of the specimens, and measure each group of specimens 5 times in parallel to take the average value.
[0064] The surface hardness of the specimens was tested using a Shore hardness tester. The hardness tester was perpendicular to the surface of the specimen to be tested, and pressure was applied and maintained for 10 seconds. Each group of specimens was tested 5 times in parallel to obtain the average value.
[0065] The test results of the example samples and the comparative example samples are shown in the following table. The tensile strength, elongation at break, total volatile organic compounds, etc. of the example of this project meet the standard of "Synthetic Surface Sports Fields for Primary and Secondary Schools" (GB 36246-2018).
[0066]
[0067]
[0068] When the mass percentage of linear SEBS is higher than 30%, the melt strength is low, the cells are prone to pores and ruptures, and the melt of the composite material cannot be foamed. When the mass percentage of linear SEBS is not higher than 30%, the melt of nonlinear SEBS / linear SEBS has a melt strength that can inhibit the escape of gas in the bubble; it can make the SEBS chain PS block form an effective PS amorphous dispersed phase in the calendering area, cooperate with the relative proportion, size and distribution of the PP grain dispersed phase, and effectively stabilize and solidify the cells.
[0069] When the mass percentage of linear SEBS is not higher than 30%, the mass percentage of ASA resin or ABS resin is lower than 5 parts, the overall relative polarity of the composite material is low, its melt viscosity is low, and its melt elasticity is large, which is not conducive to the stable growth of bubbles, and the mechanical strength of the foamed composite material is low; when the mass percentage of ASA resin or ABS resin is higher than 5 parts, its melt viscosity is high, which is not conducive to the formation of bubble nuclei. In addition, the compatibility of the composite material deteriorates, and the mechanical strength of the foamed composite material is low.
[0070] When the mass percentage of linear SEBS is not higher than 30%, the mass percentage of PP is lower than 10 parts, and it cannot produce a synergistic effect with the PS amorphous dispersed phase, and thus cannot regulate the melt strength of the composite material; when the mass percentage of PP is higher than 15 parts, the plasticity of the composite material increases and the high elasticity of the composite material decreases.
[0071] Comparative Examples 1-4 are SEBS, ASA, ABS and PP, etc., which fail to achieve good synergistic effects. The physical cross-linked network structure of the corresponding composite materials does not have effective cell locking and controlling capabilities. The melt strength is low, resulting in the escape of expanded microsphere foaming gas. Comparative Examples 1-4 fail to foam.
[0072] Comparative Example 5 is chemical foaming, and the total volatile organic matter is too high.
[0073] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A SEBS-based foamed plastic elastomer, characterized in that: Made from the following components in parts by weight:
2. A SEBS-based foamed plastic elastomer according to claim 1, characterized in that: The SEBS elastomer is composed of non-linear chain structure SEBS and linear chain structure SEBS, wherein the mass percentage of the linear chain structure SEBS is 0-30%.
3. A SEBS-based foamed plastic elastomer according to claim 1, characterized in that: The antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant DSTP, and antioxidant 618.
4. A SEBS-based foamed plastic elastomer according to claim 3, characterized in that: The antioxidant consists of antioxidant 1010 and antioxidant 168, and the mass ratio of the antioxidant 1010 and the antioxidant 168 is 2:
1.
5. A SEBS-based foamed plastic elastomer according to claim 1, characterized in that: The ultraviolet absorber is selected from one or more of UV 531, UV 770, UV 326, UV 2020, and UV 119.
6. A SEBS-based foamed plastic elastomer according to claim 5, characterized in that: The ultraviolet absorber consists of UV 531 and UV 770, and the mass ratio of the two is 2:
1.
7. A method for preparing the SEBS-based foamed plastic elastomer according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: weighing SEBS and paraffin oil respectively according to the proportion, stirring and mixing at high speed for 8 minutes; adding antioxidant and ultraviolet absorber, stirring at high speed for 3 minutes; adding expanded microspheres, stirring at high speed for 3 minutes; adding ASA resin, ABS resin, PP resin, PE wax and heavy calcium powder, stirring and mixing at high speed for 6 minutes to obtain a mixed material; and extruding the mixed material into a shape by a twin-screw extruder.
8. The method for preparing a SEBS-based foamed plastic elastomer according to claim 7, characterized in that: The rotation speed of the high-speed stirring in each step is 450±10 rpm.
9. The method for preparing a SEBS-based foamed plastic elastomer according to claim 7, characterized in that: The temperatures of each temperature zone of the twin-screw extruder are set to 170°C, 175°C, 175°C, 180°C, 185°C, 185°C, 185°C, 190°C, 190°C, 185°C, 180°C, and 180°C in sequence, and the head temperature is 175°C.
Citation Information
Patent Citations
Blending foaming material based on partially hydrogenated SEBS and preparation method thereof
CN117050457A
Wet-skid-resistant elastomer foaming material and preparation method thereof
CN117986793A